Self-deployable sail for CubeSat de-orbiting mission: preliminary design and demonstration of PANDORA - Syaril, Azrad; Yeong, Lit Yang (Aeronautical and Astronautical Society of the Republic of China, 2024)
Since the 1960s, the launching of satellites has increasingly caused the Earth's orbit to be filled with space debris travelling at very high speeds. To mitigate this problem, in 2007, the Inter-Agency Debris Coordination Committee (IADC) created a specific guideline to suggest every spacecraft, including satellites, to de-orbit itself within 25 years after the end of its mission within the Low Earth Orbit (LEO). CubeSat development and research can be cost-effective compared to larger satellite missions, making it the choice for many educational institutions to pursue space projects. However, the increasing number of CubeSat missions means that the issue of de-orbiting these microsatellites has become a pressing matter. This paper describes the design process, prototyping, and demonstration of a de-orbiting mechanism of a single-unit-size (1U) CubeSat using a passive sail membrane that is held in place by multiple booms, also named as PANDORA (Passive Sail Membrane Deployment Configuration). The multiple booms holding the thin film are released using a coil spring and Memory Alloy (SMA), which functions as a braking system, and it has been demonstrated that release took about 0.5 to 0.81 seconds. The materials used in the project are readily available and relatively low-cost considering the study, which serves as a proof of concept and is in its preliminary stage.